Pengaruh Penggunaan Media Pembelajaran Komik Digital terhadap Keterampilan Membaca Siswa Usia Sekolah Dasar - Dhea Mutiara Syahfitri; Mandra Saragih (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
This study aims to evaluate the effect of using digital comic media on the reading skills of elementary school students. This study uses a quantitative approach with a pre-experimental design and a group pretest-posttest design. The research sample consisted of all third-grade students at one of the studios in Malaysia using a purposive sampling method. The paired sample test analysis results showed a significant value (2s) of 0.000 & LT. 0.05. From these results, it can be concluded that there is a significant effect between the use of digital comic media and the reading skills of third-grade students. This study indicates that digital comic media has a positive role in improving students' reading skills. In addition, digital comic media can be used by teachers to connect learning materials with students' daily lives so that it can increase students' learning motivation. The main contribution of this study lies in the empirical evidence regarding the integration of narrative visual media in the form of digital comics that can increase students' interest and understanding of a reading. It provides opportunities for developing contextual and creative learning media in the learning process at the elementary education level.